Hawkeye no. 01, My life as a weapon - Fraction, Matt (Marvel now, 2013)
Clint Barton, a.k.a. the self-made hero Hawkeye, fights for justice and good rooftop BBQs! And with Young Avenger Kate Bishop by his side, he's out to get some downtime from being one of Earth's mightiest heroes. This is the ongoing tale of the Arrow-Avenger; Barton and Bishop mean double the Hawkeye and double the trouble!